The bidirectional association between obstructive sleep apnea and diabetic kidney disease: systematic review and meta-analysis - Zhang, Jieyu; Li, Yuandong; Dai, Bo; Nan, Zheng (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to comprehensively explore the bidirectional association between obstructive sleep apnea (OSA) and diabetic kidney disease (DKD) through a systematic review and meta-analysis.MethodSystematically search for relevant literature on the association between OSA and DKD published from database inception to September 2025. Searches were performed in the Cochrane Library, PubMed, Embase, and Web of Science. Study quality was assessed with the Newcastle-Ottawa Scale (NOS). Meta-analysis, sensitivity analysis, and publication bias assessment were conducted using Review Manager 5.4, while R software was employed to calculate prediction intervals. The certainty of evidence was evaluated using the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) framework.ResultA total of 14 articles involving 5,316 subjects were included. Patients with OSA exhibited a 1.92-fold increased risk of DKD compared with the control group (OR = 1.92, 95% CI: 1.59, 2.32, P < 0.0001). Subgroup analysis by OSA severity indicated a higher risk of DKD in patients with severe OSA (OR = 2.29) than in those with mild to moderate disease (OR = 1.52). Additionally, OSA patients showed significantly lower estimated Glomerular Filtration Rate (eGFR) levels (MD = -8.61, 95% CI: -12.92, -4.30) relative to non-OSA controls. In the reverse analysis, while the prevalence of OSA did not differ significantly between DKD and non-DKD groups (OR = 1.56, 95% CI: 0.71 - 3.43, P = 0.27), patients with DKD had significantly higher apnea-hypopnea index (AHI) (MD = 6.48, 95% CI: 1.74 - 11.22, P = 0.007) and lower average blood oxygen saturation (M-SaO2) (MD = -0.59, 95% CI: -0.82 to -0.36, P < 0.00001). No significant differences were observed in the lowest blood oxygen saturation (L-SaO2) between DKD and non-DKD groups across all subgroup analyses (all P > 0.05).ConclusionA significant bidirectional association exists between OSA and DKD, suggesting a mutual exacerbation of risks between the two conditions. These findings highlight the clinical importance of enhanced OSA screening in diabetic populations and regular renal function monitoring in OSA patients.